How is nitrogen fixation in the high arctic linked to greenhouse gas emission? - Stewart JKatherine; Brummell EMartin; Coxson SDarwyn; Siciliano DSteven (Plant and Soil, 2013)
Background and aims: Approximately 50;of belowground organic carbon is present in the northern permafrost region and due to changes in climate there are concerns that this carbon will be rapidily released to the atmosphere. The release of carbon in arctic soils is thought to be intimately linked to the N cycle through the N cycles influence on microbial activity. The majority of new N input into arctic systems occures through N2 fixation; therefore, N2-fixation may be the key driver of greenhouse gases from these ecosystems. Methods: At Alexandra Fjord lowland, Ellesmere Island, Canada concurrent measurements of N2-fixation, N mineralization and nitrification rates, dissolved organic soil N (DON) and C, onorganic soil N and surface greenhouse gas fluxes (CO2,N2O and CH4) were taken in two ecosystem types (Wet Sedge meadow and Dryas health) over the 2009 growing season (June-August). Using Structural equation modelling we evaluated the hypothesis that CO2, CH4, N2O, flux are linked to N2-fixation via the N cycle. Results: The soil N cycle was linked to CO2 flux in the Dryas Health ecosystem via DON concentrations, but there was no link between the soil n cycle and CO2 flux in the wet Sedge meadow. methane flux was also not linked to the soil n cycle, nor surface soil temperature or moisture in either ecosystem. The soil n cycle was closely linked to N2O emissions but via nitrificaton in the Wet Sedge Meadow and inorganic N in the dryas health, indicating the important role of nitrification in net N2O flux from arctic ecosystems. Conclusions: Our results should be interpreted with caution given the high variability in bith are rates of the N cycling processes and greenhouse gas flux found in both ecosystems over the growing season. However, while n2-fixation and other N cycling processes may play a more limited role in instantaneous CO2 emissions, these processes clearly play an important role in controlling N2O emissions.
Keywords: Carbon dioxide; Methane; Nitrification; Nitrogen cycle; Nitrogen fixation; Nitrogen mineralisation; Nitrous oxide; Soil moisture